Predicting language outcome at birth - Ortiz-Barajas, Maria Clemencia (Frontiers in Human Neuroscience, 2024)
Even though most children acquire language effortlessly, not all do. Nowadays, language disorders are difficult to diagnose before 3-4 years of age, because diagnosis relies on behavioural criteria difficult to obtain early in life. Using electroencephalography, I investigated whether differences in newborns' neural activity when listening to sentences in their native language (French) and a rhythmically different unfamiliar language (English) relate to measures of later language development at 12 and 18 months. Here I show that activation differences in the theta band at birth predict language comprehension abilities at 12 and 18 months. These findings suggest that a neural measure of language discrimination at birth could be used in the early identification of infants at risk of developmental language disorders.